A Response to Bruce Hindmarsh’s Diagnosing the Problem of Christian Immaturity: A Historical Perspective - Maskell, Caleb J. D. (Journal of spiritual formation & soul care, 2025)
Caleb Maskell’s response to Bruce Hindmarsh’s paper explores the enduring problem of Christian immaturity from a historical and pastoral perspective. Maskell affirms Hindmarsh’s five key impediments to maturity: weak teleology, spiritual elitism, isolation, underestimation of human brokenness, and anthropocentrism. He argues that the last—seeing Christianity as a means of self-improvement—is the root of the others. Maskell considers this concern in relationship to ecclesial models which prioritize cultural relevance but fail to challenge disciples toward theocentric maturity. He calls for a shift away from cultural accommodation born of a desire for “cultural relevance” toward churches that act as prophetic communities, prioritizing faithfulness to Christian tradition. He urges leaders to deepen their theological grounding and embrace generative conflict about anthropocentric defaults as necessary for discipleship.